Cognitive Behavior Counseling Guidebook with Self-regulated Learning Techniques to Reduce Students' Academic Procrastination Behavior - Indah Novalia; Nyoman Dantes; Putu Ari Dharmayanti (Department of Guidance and Counseling, FIP, Undiksha, 2023)
The high behavior of students' academic procrastination is shown by the attitude of students who often delay doing their daily assignments individually and in groups, stalling for time to collect assignments to the point where some students do not do their work at all. So to overcome these problems, a guidebook is needed. This study aims to develop a product in the form of a guidebook, validate the content of the guidebook, and measure the effectiveness of the self-regulated learning technique of cognitive behavior counseling guidebooks to reduce the academic procrastination behavior of SMK students. The procedure in this development research uses the 4D development procedure. In this study, three guidance counseling lecturers were involved as experts, and two guidance counseling teachers as practitioners with the task of assessing the usefulness, feasibility, and accuracy of the manual. Seven vocational students were used as subjects in a limited trial to assess the effectiveness of the guidebook. The analysis of the results of the limited trial was carried out using a t-test calculation. Data collection in the study was carried out using the questionnaire method with research instruments in the form of media validity and effectiveness test sheets. The results obtained were then analyzed using quantitative descriptive analysis techniques. The results of this study indicate that the developed guidebook has a score (CVI=0.69) in the appropriate category, and the developed guidebook effectively reduces students' academic procrastination behavior by obtaining a Sig. (2-tailed) of 0.002 < α = 0.05. The results of this study have implications for guidance and counseling services in schools.